Sarcoidosis Presenting as Massive Splenic Infarction. (30th July 2012) - Patel, Ishita; Ismajli, Mediola; Steuer, Alan
Abstract : Sarcoidosis is a multisystem granulomatous disease of unknown aetiology. Granulomatous inflammation involving the spleen is common and associated with splenomegaly. However, massive splenomegaly is a rare occurrence. Infrequently massive splenomegaly can result in splenic infarction. Massive splenic infarction in sarcoidosis has, to our knowledge, not been previously reported. We present a case of a woman presenting with massive splenic infarction and sarcoidosis confirmed by granulomatous inflammation of the liver.